Profile of the dental surgeon related to the recommendation of individual preventive strategies - Renato Pereira Silva; Carlos Alfredo de Salles Loureiro; Cássio Vicente Pereira; Flávia Martão Flório (Universidade Estadual de Campinas, 2015)
Aiming to evaluate the acquisition of scientific evidence by Dental Surgeons (DSs) and verify whether they applied it clinically, a questionnaire was sent to 223 DSs in Lavras (Minas Gerais, Brazil), containing 9 objective questions relative to confidence to recommend individual preventive strategies in Dentistry. The response rate to the questionnaires was 54.26% (n = 121). After performing logistic regression analysis (Wald Test, α = 0.05), it was found that male DSs graduated from state universities, even though they did not read text books, were more confident of prescribing and applying fluoride gel, while the DSs graduated up to 10 years and who attended in private dental office, were more confident of indicating and applying sealants. Chlorexidine was better recommended and applied by DSs postgraduated. The male DSs indicated and made better use of the Atraumatic Restorative Treatment (ART). The DSs graduated from state universities and who had not discussed technical matters with their colleagues over the last 12 months were shown to be more confident of monitoring white stain lesions with a view to the non-progression of dental caries. Thus, it was concluded that only a segment of the DSs evaluated are adequately applying the knowledge based on scientific evidence.